Predicting how climate change threatens the prey base of Arctic marine predators. (1st September 2021) - Florko, Katie R. N.; Tai, Travis C.; Cheung, William W. L.; Ferguson, Steven H.; Sumaila, U. Rashid; Yurkowski, David J.; Auger‐Méthé, Marie
Abstract: Arctic sea ice loss has direct consequences for predators. Climate‐driven distribution shifts of native and invasive prey species may exacerbate these consequences. We assessed potential changes by modelling the prey base of a widely distributed Arctic predator (ringed seal; Pusa hispida ) in a sentinel area for change (Hudson Bay) under high‐ and low‐greenhouse gas emission scenarios from 1950 to 2100. All changes were relatively negligible under the low‐emission scenario, but under the high‐emission scenario, we projected a 50% decline in the abundance of the well‐distributed, ice‐adapted and energy‐rich Arctic cod ( Boreogadus saida ) and an increase in the abundance of smaller temperate‐associated fish in southern and coastal areas. Furthermore, our model predicted that all fish species declined in mean body size, but a 29% increase in total prey biomass. Declines in energy‐rich prey and restrictions in their spatial range are likely to have cascading effects on Arctic predators. Abstract : Although research on the effects of climate change on Arctic marine ecosystems has focused on the direct impacts of sea ice decline and increased anthropogenic activity on apex species, little attention has been given to the other compounding effects of environmental change (e.g. warming waters, ocean acidification) on the prey base of predators. We modelled the indirect effects of climate change on Arctic predators and highlight how the business‐as‐usual climate change scenario drives a borealisation of the Arctic marine prey base biomass, distribution and species composition through year 2100. Declines in energy‐rich prey and restrictions in their spatial range are likely to have cascading effects on predators.